О регулярной прецессии относительно наклонной оси в задаче о движении гиростата под действием потенциальных и гироскопических сил - Щетинина, Е.К. (Нелінійні коливання, 2006)
Дослiджено умови iснування регулярних прецесiй гiростата пiд дiєю потенцiальних i гiроскопiчних сил у припущеннi, що вiсь прецесiї не збiгається з вiссю симетрiї силового поля. Отримано розв’язок рiвняння Кiрхгофа, що мiстить одну суттєву довiльну сталу. We study conditions for existence of regular processions in the motion of a gyrostat under the influence of potential and gyroscopic forces in the assumption that the procession axis does not coincide with the symmetry axis of the force field. We find a solution to the Kirchhoff equation such that it contains one arbitrary essential constant.